If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -9)(x + 7) = 0 Reorder the terms: (-9 + 2x)(x + 7) = 0 Reorder the terms: (-9 + 2x)(7 + x) = 0 Multiply (-9 + 2x) * (7 + x) (-9(7 + x) + 2x * (7 + x)) = 0 ((7 * -9 + x * -9) + 2x * (7 + x)) = 0 ((-63 + -9x) + 2x * (7 + x)) = 0 (-63 + -9x + (7 * 2x + x * 2x)) = 0 (-63 + -9x + (14x + 2x2)) = 0 Combine like terms: -9x + 14x = 5x (-63 + 5x + 2x2) = 0 Solving -63 + 5x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-7 + -1x)(9 + -2x) = 0Subproblem 1
Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7Subproblem 2
Set the factor '(9 + -2x)' equal to zero and attempt to solve: Simplifying 9 + -2x = 0 Solving 9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 0 + -9 -2x = 0 + -9 Combine like terms: 0 + -9 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5Solution
x = {-7, 4.5}
| 15+27-23=d-32 | | 92=2(x+x+4) | | 5[-3(3x+5)+3(5x-3)]= | | -5v+6=-19 | | 2y^2+x^2-4y-18=0 | | W+-6=10 | | K+10=30 | | H(t)=-16t^2+48t+50 | | 5+8p=-147 | | t^3-4t^2+7t+3=0 | | 5+8-p=-147 | | M+-10=10 | | 4x+20=3x+6 | | 9s-44=2s+5 | | 48+8y=16y+16 | | 9x+6(100)=7x+700 | | (q+33)+6q=180 | | M+-5=-10 | | z+12=5z | | 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 |